The shocking state of apatite and merrillite in shergottite Northwest Africa 5298 and extreme nanoscale chlorine isotope variability revealed by atom probe tomography. (15th January 2021) - Darling, J.R.; White, L.F.; Kizovski, T.; Černok, A.; Moser, D.E.; Tait, K.T.; Dunlop, J.; Langelier, B.; Douglas, J.O.; Zhao, X.; Franchi, I.A.; Anand, M.
Highlights: Chlorapatites and merrillites in NWA 5298 have a wide-range of shock nanostructures. Shock features in apatite are linked to elemental and chlorine isotope heterogeneity. Atom probe tomography can yield accurate chlorine isotope data at ‰ precision. Nanoscale boundaries contain isotopically light chlorine mobilized during shock. The primary chlorine isotopic composition of NWA 5298 is −0.3 ± 0.6 ‰ (2σ) Abstract: The elemental and chlorine isotope compositions of calcium-phosphate minerals are key recorders of the volatile inventory of Mars, as well as the planet's endogenous magmatic and hydrothermal history. Most martian meteorites have clear evidence for exogenous impact-generated deformation and metamorphism, yet the effects of these shock metamorphic processes on chlorine isotopic records contained within calcium phosphates have not been evaluated. Here we test the effects of a single shock metamorphic cycle on chlorine isotope systematics in apatite from the highly shocked, enriched shergottite Northwest Africa (NWA) 5298. Detailed nanostructural (EBSD, Raman and TEM) data reveals a wide range of distributed shock features. These are principally the result of intensive plastic deformation, recrystallization and/or impact melting. These shock features are directly linked with chemical heterogeneities, including crosscutting microscale chlorine-enriched features that are associated with shock melt and iron-rich veins. NanoSIMS chlorine isotope measurements of NWA 5298 apatite reveal a range of δ 37 Cl values (−3 to 1‰; 2σ uncertainties <0.9‰) that is almost as large as all previous measurements of basaltic shergottites, and the measured δ 37 Cl values can be readily linked with different nanostructural states of targeted apatite. High spatial resolution atom probe tomography (APT) data reveal that chlorine-enriched and defect-rich nanoscale boundaries have highly negative δ 37 Cl values (mean of −15 ± 8‰). Our results show that shock metamorphism can have significant effects on chemical and chlorine isotopic records in calcium phosphates, principally as a result of chlorine mobilization during shock melting and recrystallization. Despite this, low-strain apatite domains have been identified by EBSD, and yield a mean δ 37 Cl value of −0.3 ± 0.6‰ that is taken as the best estimate of the primary chlorine isotopic composition of NWA 5298. The combined nanostructural, microscale-chemical and nanoscale APT isotopic approach gives the ability to better isolate and identify endogenous volatile-element records of magmatic and near-surface processes as well as exogenous, shock-related effects.